A SHIFT OPERATOR APPLICATION ON INEQUALITIES IN \(\ell^2\) SPACE - Borogovac, M. (Matematichki Bilten, 1993)
In this note some inequalities in the complex space \(\ell^2\) are proved. It is done by means of the shift and differential operators in \(\ell^2\). The results are generalisations and improvements of results from [1]. These inequalities from [1] are repeated in the Introduction.